The Polish family under Stalinist subjugation - Kryńska, Elwira Jolanta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The situation of Polish families during Stalinist subjugation was particularly arduous. The family was treated as an important part of the political system’s socialization which was not rooted at all in the sphere of traditional values and norms developed in the process of historical progress of the Polish statehood. Due to the foundations of Latin civilization based on personalization that were cherished by Polish families, cynical endeavors to take away freedom, legal capacity and personal property – the objectives which Stalinism aimed at both indirectly and directly – failed, which destroyed the communists’ plans. The family did not cease to be the most important centre of human life and development. Theoreticians of a „new deal” did not manage to limit the family to the role of a „basic social unit” of „socialist morality”.
Keywords: family; Stalinism; subjugation